Development and psychometric testing of the modeling scale for novice nurses: a cross-sectional survey design - Yayoi Nagano; Yasuko Hosoda (BMC Nursing)
Abstract Background Modeling is the learning of new patterns of behavior by observers through observation. In order for novice nurses to learn effectively in a busy, multi-tasking clinical environment, they need a learning strategy that is integrated into their daily work. Modeling is a necessary learning strategy for nurses because they learn skills, knowledge, and attitudes by observing senior nurses in action. In nursing, it is important to learn skills, knowledge, and attitudes by observing the behavior of senior colleagues. However, previous studies have shown that there are situations in which modeling is not done smoothly. Therefore, in this study, we decided to develop a modeling self-assessment scale to assist novice nurses in modeling. Methods 1,457 novice nurses from a random sample of 103 hospitals in Japan were selected, of which 337 novice nurses were surveyed from November 2019 to January 2020 by anonymous questionnaire. The questionnaire consisted of the draft Modeling Scale for Novice Nurses, The Scale Measuring a Sense of Generalized Self-Efficacy and a simplified version of the Scale of Self-Regulated Learning Strategy for Nurses for review of criteria-related relevance to the Modeling Scale for Novice Nurses, and personal background. Factor analysis was used for analysis, and correlation coefficients were calculated for criterion-related validity. For stability, the number of intraclass correlation coefficients were calculated for consenting subjects by retesting method 3 weeks after their responses. Results The demographics of the participants were 316 women and 21 men, with a mean age of 22.7 ± 1.8 years. Item and factor analyses yielded 21 items with four subscales. Cronbach’s α coefficient for the 21 items was 0.930. The correlation coefficients for the Modeling Scale for Novice Nurses and the Scale of Self-Regulated Learning Strategy for Nurses ranged from 0.266 to 0.480. In the retest method, the intraclass correlation coefficient ranged from 0.771 to 0.786. Conclusions The Modeling Scale for Novice Nurses can be used to obtain novice nurses’ self-assessment of modeling and to assist novice nurses in modeling smoothly.